Rationalization of Network Segregation for Continuity of Financial Services following COVID-19 - Choi, Manyong; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2021)
As measures for protecting users and ensuring security of electronic financial transactions, such as online banking, financial institutions in South Korea have implemented network segregation policies. However, a revision of such domain-centered standardized network segregation policies has been increasingly requested because of: 1) increased demand for remote work due to changes resulting from COVID-19 pandemic; and 2) the difficulty of applying new technologies of fintech companies based on information and communications technologies (ICTs) such as cloud services. Therefore, in this study, problems of the remote work environment arising from the network segregation policy currently applied to the financial sector in South Korea and those from the application of new ICTs such as fintech technology have been investigated. In addition, internal network protection policies of foreign financial sectors, such as those of the United States, United Kingdom, European Union, and Russia, and internal network protection policies of non-financial sectors, such as control systems, have been analyzed. As measures for the effective improvement of the current network segregation policy, we propose a policy change from domain-based to data-centric network segregation. Furthermore, to resolve threats of hacking at remote work, recently emerging as a global problem due to COVID-19 pandemic, a standard model for remote work system development applicable to financial companies and a reinforced terminal security model are presented, and an alternative control method applicable when network segregation is not applied is proposed.
Keywords: COVID-19; Financial sectors; Financial service; Internal network; Network protection; Network segregation; Protection policy; Rationalisation; Remote work; South Korea; COVID-19; Financial service; Information security; Network segregation; Remote work